The mysterious morphology of MRC0943-242 as revealed by ALMA and MUSE - Gullberg, B.; De Breuck, C.; Lehnert, M.; Vernet, J.; Bacon, R.; Drouart, Guillaume; Emonts, B.; Galametz, A.; Ivison, R.; Nesvadba, N.; Richard, J.; Seymour, Nick; et al. (2016)
© 2016 ESO. We present a pilot study of the z = 2.923 radio galaxy MRC0943-242, where we combine information from ALMA and MUSE data cubes for the first time. Even with modest integration times, we disentangle the AGN and starburst dominated components. These data reveal a highly complex morphology as the AGN, starburst, and molecular gas components show up as widely separated sources in dust continuum, optical continuum, and CO line emission observations. CO(1-0) and CO(8-7) line emission suggest that there is a molecular gas reservoir offset from both the dust and the optical continuum that is located ~90 kpc from the AGN. The UV line emission has a complex structure in emission and absorption. The line emission is mostly due to a large scale ionisation cone energised by the AGN, and a Lya emitting bridge of gas between the radio galaxy and a heavily star-forming set of components. Strangely, the ionisation cone has no Lya emission. We find this is due to an optically thick layer of neutral gas with unity covering fraction spread out over a region of at least ~100 kpc from the AGN. Other less thick absorption components are associated with Lya emitting gas within a few tens of kpc from the radio galaxy and are connected by a bridge of emission. We speculate that this linear structure of dust, Lya and CO emission, and the redshifted absorption seen in the circum nuclear region may represent an accretion flow feeding gas into this massive AGN host galaxy.